Data of Project on Atmospheric Circulation and Material Cycle in the Antarctic, Part 1. : Aerological Sounding Data at Dome Fuji Station in 1997 - Hirasawa, Naohiko; Hayashi, Masahiko; Kaneto, Susumu; Yamanouchi, Takashi (National Institute of Polar Research, 1999)
P(論文) departmental bulletin paper